Effect of teacher encouragement during deep learning on attention and volleyball techniques among students at high school physical education - Bachtiar; Lestari, Ade Tuti; Nurina, Titis; Adil, Ahmad; Setiawan, Edi (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2025)
Background: Teacher Encouragement during Deep Learning (TEDL) based on literature has a positive impact, but it is not yet clear how it affects attention and volleyball technique among students. Objectives: Therefore, the current study aims to analyze the effects of TEDL on improving attention and volleyball techniques among students in physical education (PE) classes. Methods: An experimental method with a pretest-posttest design was adopted in this study. Forty participants were involved, representing students from several high schools in Sukabumi (Indonesia). They were recruited using inclusion criteria and randomly assigned to the TEDL group (n = 20) and the control group (CG) (n = 20). Assessment of attention and basic volleyball techniques was measured at the pretest and posttest stages. Finding/Results: The results of our study show that there are significant main effects of teaching (p < 0.05), time (p < 0.05) and interaction (p < 0.05) on attention and volleyball techniques. Conclusion: We firmly conclude that TEDL can be an alternative teaching model to replace traditional learning in improving attention and volleyball techniques among students. Future research is expected to design TEDL programs for other teaching materials such as basketball, soccer, futsal, swimming, hockey, or badminton.